أهل الحل والعقد دراسة في المفهوم والنشأة وإمكانات التطبيق في العصر الحديث: Ahlu al-Hall wa al-A’qd (The members of the Parliament): A study on the concept, origin and potential applicability in contemporary time - الأحمر المختار (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 2017)
تهدف هذه الدراسة إلى مقاربة موضوع أهل الحل والعقد بالوقوف على سياقه التاريخي من حيث النشأة والمفهوم، وكشف أسسه المعرفية والتعاقدية، وكيف ظلَّت الأمةُ بتمثُّلها قاعدة الشورى المنظَّمة مصدرَ بناء المفهوم. وهو مفهوم يُبرِز -من منظور التجربة التاريخية الإسلامية- أنَّ فكرة التمثيل والنيابة قد ظهرت مبكراً في الفعل الاجتماعي والسياسي الإسلامي. تهدف الدراسة أيضاً إلى البحث في علاقة مفهوم أهل الحل والعقد بما تطرحه نظرية النظم السياسية الحديثة، وإمكانية الإفادة منها في تجنُّب بعض عيوب نظام التمثيل الديمقراطي الحديث أو إصلاحها، باقتراح أنموذج مؤسسي يُعبِّر عن مضمون هذا المفهوم. This study aims to approach the traditional Islamic concept called "Ahlu al-Hall wa al-A’qd" that may be considered today as members of the parliament by investigating the historical context in terms of origination, revealing its conceptual and contractual foundations and how the nation (Ummah) has been the source of building the concept through the systematic practice of consultancy (Shura). Besides, in the Islamic historical experience, this concept shows that the idea of representation and deputation have appeared early in the Islamic social and political action. Furthermore, the study examines the relationship of the concept of "Ahlu al-Hall wa al-A’qd" with the theory of modern political systems and explore the possibility of using it to avoid or reform some of the defects of the modern democratic representation system by proposing an organizational model that reflects the essence of this concept.